Blockchain-Based EHR Hospital Management System: A Decentralized Solution for Healthcare Services - Ravanaboina Sankeerthana; P. Vinaya Sree; G. Vishnu Murthy (Utilitas Mathematica, 2025)
Advancement in the hospital management system is due to the incessant pressure to meet the ever-increasing need of secure, transparent, and effective healthcare. The proposed paper introduces a decentralized Electronic Health Record (EHR) Hos- pital Management System constructed on Ethereum blockchain with the help of Ganache. The system will have six special portals, which include: User, Doctor, Admin, Lab, Insurance and Phar- macy that may be considered as crucial in provision of hassle- free healthcare services. Safe access is ensured as the user just has to undergo the two-factor authentication method involving email OTP and an administrator release. After the verification is done, patients can create an appointment with doctors, check repair insurance, view lab results, and order drugs. The doctors receive the options of booking and cancellation of appointments, ordering lab tests, checking insurance history, and keeping track of bed availability. Doctors make test requests in the lab portal and upload the results and the insurance portal is used to process policy application and claims. The pharmacy module has facilities of inventory and selling medicines as per prescription. One of the outstanding features of the system is the fusion of the blockchain technology. Through Ethereum and Ganache, all the important medical records accessible are stored in a secure way and they cannot be tampered with, they also maintain data integrity, data security and data transparency. All transactions in the modules are automated and tracked in a tamper-proof trail by smart contracts. The application is being built with the Python, Django, HTML, CSS, JavaScript, Bootstrap, and MySQL stacks, and the blockchain communications occur through Web3. This central- free design does improve reliability and accountability of work by hospitals and can serve as a future-proof model of digital provision of healthcare services.